Maneuvering target imaging and scaling by using sparse inverse synthetic aperture - Xu, Gang (2017)
In recent years, there have been increasing interests in addressing the issue of high-resolution inverse synthetic aperture radar (ISAR) imaging from sparse aperture (SA) data. The non-uniform rotation property of maneuvering target introduces non-stationary echo modulation to exhibit two-dimensional (2-D) migration through resolution cells (MTRC), which increases the difficulty of SA-ISAR imaging. In this paper, we focus on ISAR imaging and scaling of maneuvering target for effective MTRC correction and SA synthesis. Under a scaled non-uniform Fourier dictionary to include MTRC, SA maneuvering target imaging is formatted as sparse representation with maximum a posterior (MAP) estimation. Then, sparse ISAR imaging joint with parameter estimation is solved by using a two-step procedure. The estimated rational parameters are used to rescale the reconstructed ISAR image to extract the 2-D target geometry. Finally, the experiments based on simulated and measured data are performed to confirm the effectiveness of the proposed algorithm.